Comparison of the Effectiveness of Mindfulness-Based Cognitive-Behavioral Therapy and Reality Therapy on Emotional Regulation and Self-Efficacy in Women Seeking Divorce - Yahyavi Gargari, Roghayeh; Farshbaf Maneisefat, Farnaz; Etemadnia, Mahin (Psychology of Woman Journal, 2024)
Objective: This study aimed to compare the effectiveness of mindfulness-based cognitive-behavioral therapy and reality therapy on emotional regulation and self-efficacy among couples seeking divorce.Methods and Materials: The present research was a quasi-experimental study with a pre-test, post-test, and follow-up design, including a control group. The population consisted of all couples seeking divorce referred by the judiciary to the psychodynamic center of Jolfa city from spring to winter 2021. The sample comprised 60 individuals chosen through purposive sampling and randomly assigned to three groups of 20. Following sampling, two experimental groups received either group mindfulness-based cognitive-behavioral therapy in eight 90-minute sessions (weekly) or group reality therapy in eight 90-minute sessions (weekly), while the control group received no intervention. Data were collected using the Garnefski and Kraaij Cognitive Emotion Regulation Questionnaire (CERQ-P-short) and the Sherer Self-Efficacy Questionnaire (DCI-SF). Data analysis was performed using mixed repeated measures ANOVA and Bonferroni post-hoc tests with SPSS version 24.Findings: The findings indicated that there was a significant difference between the overall means of emotional regulation and self-efficacy in both the mindfulness-based cognitive-behavioral therapy and reality therapy groups, with mindfulness-based cognitive-behavioral therapy having a greater impact on emotional regulation and self-efficacy (P